2013
DOI: 10.1073/pnas.1218206110
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and functional characterizations of phosphodiesterase subtype 4D in human cancers

Abstract: Discovery of cancer genes through interrogation of genomic dosage is one of the major approaches in cancer research. In this study, we report that phosphodiesterase subtype 4D (PDE4D) gene was homozygously deleted in 198 cases of 5,569 primary solid tumors (3.56%), with most being internal microdeletions. Unexpectedly, the microdeletions did not result in loss of their gene products. Screening PDE4D expression in 11 different types of primary tumor samples (n = 165) with immunohistochemistry staining revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 29 publications
(23 reference statements)
8
77
0
Order By: Relevance
“…6A-C). The involved locus spanned ;2 Mb in length and disrupted genomic structures of several genes including ACTBL2 and a candidate oncogene, PDE4D (Lin et al 2013). …”
Section: Resolving Focal Genomic Amplifications and Rearrangementsmentioning
confidence: 99%
“…6A-C). The involved locus spanned ;2 Mb in length and disrupted genomic structures of several genes including ACTBL2 and a candidate oncogene, PDE4D (Lin et al 2013). …”
Section: Resolving Focal Genomic Amplifications and Rearrangementsmentioning
confidence: 99%
“…This study showed a connection between PDE4D and AMPK in cancer/cellcycle dynamics (46). Further depletion of PDE4D can cause apoptosis (10%-40%) in multiple types of cancer cells which have elevated expression level of PDE4D (26).…”
Section: Discussionmentioning
confidence: 63%
“…2D). The overexpression of PDE4D has been observed in multiple types of cancer cells originating from the central nervous system (CNS), lung, breast, and melanomas (26). But, so far, there has been no report that the elevated expression of PDE4D is mutation-specific in cancer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations